Knowledge, attitude and utilization of emergency contraception: a cross sectional study among female university and college students - Firdawek, Ewnetu; Aragu, Dayan; Konale, Mekdes (Ethiopian Journal of Reproductive Health, 2018)
Abstract Introduction: Although emergency contraception is an essential reproductive health option, it remains vastly underutilized. Objectives: The objective of this study was to assess the level of knowledge, attitude and utilization of emergency contraception (EC) and its associated factors. Methods: Cross sectional survey was conducted on female university and college students in Arba Minch town from November 15 -30, 2009. Self-administered questioners were employed to collect pertinent data. Results: From a total of 791 respondents, 66.2% of them had reported that they have ever heard about emergency contraception and 60.1% of them reported incorrect methods like Depo- Provera and Norplant and 26 % of them don’t know the exact time when EC should be taken. For most of the respondents the source of information on EC was peer discussion, 185 (35.3%) followed by from health professional teaching, 101(19.3%) from teachers 96(18.3%) and from mass media66 (12.6%). Out of the 791 respondents only 76 (9.6 %) of them have practiced EC and majority of them 65(85.5%) used pills. Only 8 (10.5 %) of those who used EC know the correct method use following unprotected sex. Most of the respondents 530 (67%) are willing to use EC and for majority of them 494(93.2%), the reason mentioned was preference to use EC than getting pregnancy. Conclusion: Knowledge and utilization of EC was low, but attitude on EC was relatively high. Pills have been used widely by most of the respondents as an EC method (Ethiopian Journal of Reproductive Health , 2012,6(1): 37-45).